URBAN GOVERNANCE REIMAGINED: SOCIOECONOMIC DYNAMICS AND INFRASTRUCTURAL OVERHAUL IN THE ADMINISTRATION OF JAKARTA UNDER THE LEADERSHIP OF ANIES BASWEDAN - Gunawan Widjaja (Adisam Publisher, 2024)
This study explores the transformative shifts in urban governance, socioeconomic dynamics, and infrastructural development during the tenure of Anies Baswedan as the Governor of Jakarta. Through a comprehensive literature review, it examines the multifaceted impacts of Baswedan's leadership on Jakarta's urban landscape. Baswedan's administration has been marked by ambitious policies addressing social inequalities, promoting economic growth, and enhancing infrastructure. Initiatives such as the Jakarta Smart City program, the One Million Trees Movement, and the Jakarta MRT expansion have sought to modernize governance, foster environmental sustainability, and improve the quality of life for residents. However, challenges persist in social welfare, economic inclusion, and sustainable development, underscoring the complexities of governing a rapidly growing megacity. This study contributes to a deeper understanding of urban governance paradigms by synthesizing insights from diverse disciplinary perspectives. It offers valuable insights into the opportunities and challenges of leadership in dynamic urban contexts.